Effects of almond intake on oxidative stress parameters: A systematic review and meta-analysis of clinical trials - Bingfeng Luo; Walid Theib Mohammad; Abduladheem Turki Jalil; Marwan Mahmood Saleh; Muataz Mohammed Al-Taee; Mohammad Y. Alshahrani; Naseer Mihdi Mohammed; Ammar Heydani (Elsevier, 2023)
Background and aims: Several randomized controlled trials (RCTs) have shown that almonds can improve oxidative stress indices, but the results are controversial. Therefore, the goal of this research was to carry out a systematic review and meta-analysis of all RCTs that evaluated the effect of almonds on selected oxidative stress indices. Methods: A systematic search was conducted up to April 2022 on PubMed, Scopus, Web of Science, and Google Scholar. We have selected the studies that investigated the effects of almonds on malondialdehyde (MDA), and oxidized low-density lipoprotein (Ox-LDL) levels in adults. Data were pooled by using the random-effects model. The risk of bias in individual studies was assessed using the Cochrane Collaboration risk of bias tool. Results: Seven RCTs involving 424 participants were analyzed. The results indicated that almond intake led to a significant decrease in MDA levels (WMD: − 6.63 nmol/ml; 95 % CI: − 8.72 to − 4.54; P < 0.001). However, no significant effect was observed on Ox-LDL (Hedges' g: − 0.12; 95 % CI: − 0.34 to 0.10; P = 0.28). Sensitivity analysis showed that overall estimates were not affected by the elimination of any study. We did not observe any evidence regarding publication bias. Conclusion: The present meta-analysis suggests that almond intake can improve MDA levels and might play a beneficial role in the reinforcement of the antioxidant defense system and amelioration of oxidative stress in adults. There is a need for more studies with larger groups to better estimate this effect.